Human Milk Versus Formula Feeding Among Preterm Infants: Short-Term Outcomes - Maayan-Metzger, Ayala; Avivi, Shirli; Schushan-Eisen, Irit; Kuint, Jacob (American Journal of Perinatology, 2012)
We evaluated short-term neonatal outcomes among preterm infants according to type of feeding administered (human milk or formula). Retrospective data were collected on 400 preterm infants at gestational age ≤32 weeks. Groups were chosen and compared according to feeding type. The premature infants who were fed human milk had lower gestational age and birth weight than those who were formula fed. Lower rates of necrotizing enterocolitis (NEC) were detected in the group of infants fed human milk (p = 0.044). Lower rates of retinopathy of prematurity (ROP) were detected in a subgroup of breast-fed infants born at 24 to 28 weeks’ gestational age, but the results did not reach statistical significance using univariate analysis (p = 0.06). Using multivariate analysis, however, ROP stage III among this subgroup was significantly lower (p = 0.022). No differences were recorded for other neonatal complications such as infections or for growth parameters. The advantage of human milk feeding, found mainly among preterm infants with respect to rates of NEC and ROP, supports efforts to encourage mothers to feed their infants human milk.
Keywords: neonatal nutrition; neonatal outcome; preterm infants